Cheering for 'our' champs by watching 'sexy' female throwers: Representation of nationality and gender in Slovenian 2008 Summer Olympic television coverage. (August 2013) - Ličen, Simon; Billings, Andrew C
Television is a cultural service and its national renderings of the Olympic Games contribute to the viewers' understanding of themselves and the world. This study examines the representation of nationality and gender within Slovenian broadcasts of the 2008 Beijing Olympics. Results show that evaluative commentary comprised as much as 44% of the dialogue. 'Home' athletes were given more prominence, while foreign athletes were largely portrayed through quantifiable features. Male athletes received more commentary than females. Announcers favoured analysing results and predicting outcomes for men, and resorted to personality and physicality depictions in women. A critical discourse analysis uncovered notions about gender and nationality that would be deemed inappropriate in many societies. Sports journalists and broadcasters at TV Slovenija do not have explicit editorial policies addressing chauvinistic dialogue. The absence of a policy is not perceived as an issue as individual announcers abide to their personal, at times conflicting, understandings of proper announcing.